Vygotsky's socio-cultural theory of literacy; Scaffolding children to read and write at an early age - Arshad, Mahzan; Chen, Wu Hsueh (UI Scholars Hub, 2009)
In the article the concept of semiotic mediation, appropriation, internalization, Zone of Proximal Development (ZPD) and scaffolding in particular were reviewed to provide understanding of the process. Under the concept of semiotic mediation, the issue of how children learn through imitating adults was examined with inputs from second language acquisition theories. Vygotsky's concept of appropriation provides the springboard for a discussion on how children may appropriate the psychological tool of language through modeling and text meditation in the context of second language learning. It is hoped that the understanding of these concepts could lead to more insights in order to understand the various changes observable in children at early age as they nudge to achieve their potential in their literacy development. The information gathered in the paper may be used by parents or teachers in preschool as the foundation to help children acquire literacy skills at early age.